Estudo taxonômico de Achilixiidae Muir, 1923 (Hemiptera: Auchenorrhyncha: Fulgoroidea) no Brasil - Viegas, Eduarda Fernanda Gomes (Instituto Nacional de Pesquisas da Amazônia - INPA, 2019)
Achilixiidae is a small family including 24 species distributed into two genera: Achilixius Muir, 1923 (16 species) from Oriental region and Bebaiotes Muir, 1924 (8 species) from the Neotropical region. Bebaiotes is distinguished from Achilixius by the frons lacking the median carina, vein R without ramification close to the anterior margin, veins CuA1 and CuA2 not fused close to the posterior margin, and a pair of lateral abdominal processes forming three pits. None species of Achilixiidae has been registered for Brazil so far, with only Bebaiotes registered for Panama, Ecuador, and Guiana in the Neotropics. The material studied was obtained from national zoological collections and photos were provided by some foreign collections. An identification key, maps with geographical records, descriptions, and redescriptions of the species were provided. Four new species were revised and their distribution widen: Bebaiotes banksi (Metcalf, 1938) (Brazil - Amazonas and Pará; Panama); Bebaiotes dorsivittata Fennah, 1947 (Brazil - Amapá, Amazonas, Pará, Rondônia and Roraima; Ecuador; Peru; Bebaiotes guianesus (Fennah, 1947) (Brazil - Amazonas; Guiana); Bebaiotes pulla Muir, 1934 (Brazil - Acre and Amazonas; Ecuador) and it have been added eight new species for the genus for Brazil: Bebaiotes amazonica sp. nov. (Amazonas, Pará, Rondônia and Roraima); Bebaiotes bia sp. nov. (Acre); Bebaiotes dichromata sp. nov. (Amazonas); Bebaiotes macroptera sp. nov. (Amazonas and Amapá); Bebaiotes parallela sp. nov. (Amazonas); Bebaiotes pennyi sp. nov. (Amazonas and Maranhão); Bebaiotes tigrina sp. nov. (Amazonas); Bebaiotes wilsoni sp. nov. (Amazonas). The distribution of the family and genus were expanded for Brazil, being centered in Northern and Northeastern regions.
Keywords: Fulgoromorpha; Região Neotropical; Bebaiotes